Вивчення вмісту біохімічних маркерів метаболізму кісткової тканини в ротовій рідині хворих на генералізований пародонтит - Возна, Ірина Володимирівна; Самойленко, А. В.; Павлов, Сергій Васильович; Vozna, I. V.; Samoilenko, A. V.; Pavlov, S. V. (Українська медична стоматологічна академія, 2020)
Мета роботи – визначення концентрації в ротовій рідині вмісту вітаміну D, маркерів деструкції кісткової тканини й оцінка діагностичної значущості цих показників для оптимізації спеціальних програм діагностики і профілактики основних стоматологічних хвороб у жителів промислового регіону. Біохімічні маркери дозволяють виявити порушення метаболізму кісткової тканини, а рівень їхньої концентрації залежать від ступеня тяжкості пародонтиту. У пацієнтів із захворюваннями тканин пародонта, які працюють у шкідливих умовах виробництва, дефіцит і недостатність вітаміну D, концентрація VDBP, ММР-8, остеокальцину виражені більшою мірою, ніж у пацієнтів без шкідливих чинників. Отримані результати обґрунтовують доцільність упровадження імуноферментного дослідження вітаміну D, VDBP, ММР-8, остеокальцину в лабораторний скринінг захворювань тканин пародонта в ролі високоінформативних біохімічних маркерів діагностики і прогнозу. The study aims to determine the concentration of vitamin D in the oral fluid, markers of bone destruction as well as to assess the diagnostic value of these indicators to optimize special programs for diagnostics and prevention of major dental diseases in the industrial region’s residents. The object and research methods. There were examined 178 patients. The study group consisted of 126 patients with generalized periodontitis of initial (8), I (32), II (68), and III (18) severity levels, chronic course who are working in hazardous conditions of the "Dniprospetsstal" plant in Zaporizhzhya. The comparison group included 32 patients with periodontitis of initial (5), I (10), II (11), and III (6) severity degrees, which do not have occupational health risks. The control group consisted of 20 relatively healthy individuals without signs of periodontal tissue disease. The level of vitamin D, VDBP, MMP-8, and osteocalcin was determined by enzyme-linked immunosorbent assay. Research results. It is established, that the patients with the initial severity of periodontal disease have minor vitamin D deficiency and as the severity progresses, the vitamin D deficiency increases. Therefore, in the third severity of the inflammatory process, there is a severe deficiency of vitamin D. It should be noted that in the study group patients who were working in hazardous production conditions, the decrease of vitamin D content in the oral fluid was more pronounced relative to the patients in the comparison group with periodontal disease and no occupational hazards. Vitamin D deficiency depends on the severity of periodontitis, which is confirmed by the established strong feedback of the comparison group (γ = -0.790, p <0.05), and that of the study group (γ = -0.778, p <0.05). Periodontitis was accompanied by a significant loss of vitamin D and was associated with a sharp decrease of VDBP protein. That is, not only the concentration of vitamin D changes but so does the protein responsible for the transfer and utilization of this vitamin. We have found a correlation between the VDBP presence in the sample and the severity of periodontitis. Strong feedback of the comparison group (γ = -0.962, p <0.05) and that of the study group (γ = -0.966, p <0.05) was detected. The patients had impaired bone tissue metabolism, which was accompanied by the bone destruction marker MMP-8 increase. The obtained data show a significant increase of MMP-8 content in the oral fluid in periodontitis patients, compared to the individuals with clinically intact periodontium, and reliably reflects the severity of the disease. We have established a direct strong connection between the level of MMP-8 in the oral fluid and the degree of the disease using the method of mathematical analysis. The correlation coefficient was (γ = 0.892, p <0.05) in the comparison group and (γ = 0.965, p <0.05) in the study group. The results of studying bone tissue formation activity considering the level of osteocalcin have shown that osteocalcin decreases with increasing severity of the disease. The correlation between osteocalcin levels and disease severity in the patient groups had strong feedback both in the comparison group (γ = -0.919, p <0.05) and in the study group (γ = -0.987, p <0.05). Conclusions. 1. Biochemical markers allow detecting disorders of bone tissue metabolism and their level of concentration depends on the severity of periodontal tissue disease. 2. The vitamin D deficiency, the concentration of VDBP, MMP-8, osteocalcin are more pronounced in the patients with periodontal disease experiencing occupational hazards compared to the patients who are not exposed to such conditions. 3. The obtained results substantiate the feasibility of enzyme-linked immunosorbent assay introducing vitamin D, VDBP, MMP-8, osteocalcin in laboratory screening of periodontal tissue diseases as highly informative biochemical markers used for diagnostics and prognosis.
Study of biochemical markers’ content of bone tissue metabolism in the oral liquid of patients with generalized periodontitis
Keywords: пародонтит; біохімічні маркери; метаболізм кісткової тканини; periodontitis; biochemical markers; bone tissue metabolism